Analysis of the Influence of Education, Capital, and Information Technology on the Income of Informal Sector E-Commerce Users in Denpasar City - I Gusti Agung Ayu Cintya Nandari; Ida Ayu Nyoman Saskara (International Journal of Economics, Commerce, and Management, 2025)
As an archipelagic nation with the fourth largest population in the world, Indonesia faces challenges in employment opportunities due to the imbalance between population growth and job availability. Consequently, both central and regional governments are now focusing on the development of the informal sector, which contributes significantly to the economy and employment creation. In the era of the digital economy, this sector benefits from technological advancements. However, informal entrepreneurs continue to face obstacles such as limited access to technology, human resources, and capital. This study aims to examine the influence of education, capital, and information technology on the income of informal sector actors who utilize e-commerce in Denpasar City, both simultaneously and partially. The data used in this study consists of both primary and secondary sources, collected through interviews with 100 respondents selected using purposive sampling. The analytical methods employed include descriptive analysis and multiple linear regression analysis. The results show that the variables of education, capital, and information technology simultaneously have a significant influence on the income of the informal sector. Partially, each of these variables also exerts a positive and significant influence on income. Based on these findings, it is recommended to increase attention to education and training in digital technology utilization, as well as improve access to capital for informal entrepreneurs. These efforts can enhance sales performance, expand market reach, and consequently increase income.